First, we need to find the common difference, denoted by 'd', of the arithmetic progression (AP).
We are given that the 10th term is -27 and the 5th term is -12.
To find the common difference, we can use the formula for the nth term of an AP:
an = a1 + (n-1)d
where an is the nth term, a1 is the first term, and d is the common difference.
Using the information given, we have:
-27 = a1 + (10-1)d ... (1)
-12 = a1 + (5-1)d ... (2)
Solve equations (1) and (2) simultaneously.
From equation (2), rearrange to express a1 in terms of d:
a1 = -12 - 4d ... (3)
Substitute equation (3) into equation (1):
-27 = (-12 - 4d) + (10-1)d
-27 = -12 - 4d + 10d - d
-27 = -12 + 6d
Rearrange the equation:
6d = -27 + 12
6d = -15
d = -15/6
Simplify d:
d = -5/2
Now, we know that d = -5/2.
To find the sum of 25 terms, we will use the formula for the sum of an AP:
Sn = (n/2)(2a1 + (n-1)d)
where Sn is the sum of the first n terms.
Substituting in the given values, we have:
S25 = (25/2)(2a1 + (25-1)d)
Simplify:
S25 = (25/2)(2(-12 - 4d) + (25-1)d)
Simplify further by substituting the value of d:
S25 = (25/2)(2(-12 - 4(-5/2)) + (25-1)(-5/2))
Simplify and calculate:
S25 = (25/2)(2(-12 + 10) - (24)(5/2))
Simplify further:
S25 = (25/2)(2(-2) - 60/2)
S25 = (25/2)(-4 - 30)
S25 = (25/2)(-34)
Multiply:
S25 = -425
Therefore, the sum of the 25 terms of the AP is -425.
If the 10th term of an Ap is -27 and the 5th term is -12
What will be the sum of its 25 terms ?
1 answer